2012
DOI: 10.1155/2012/383812
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Relationship between Economic Growth and Government Size

Abstract: The purpose of this paper is to explore the association between government size and economic growth in the United States using time-series data over the period 1950–2007. In particular, this paper examines the effects of two key components of government expenditure, namely, government consumption and government investment, on US economic growth. A simultaneous-equation model is used to deal with the problem of bi-directional relationship between government size and economic growth. The results suggest that an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Other studies that are not in line with these findings include Al-Shatti (2014) in Jordan who concluded that government spending in the short and long term has no significant effect on economic growth. In addition, the study of Rauf et al (2012) in Pakistan, a study by Ray and Ray (2012) in India and Ghosh (2012) which concluded that there is no causal relationship between economic growth and government spending in Pakistan and India. That is, these three studies do not support the Keynesian hypothesis or Wagner's law.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies that are not in line with these findings include Al-Shatti (2014) in Jordan who concluded that government spending in the short and long term has no significant effect on economic growth. In addition, the study of Rauf et al (2012) in Pakistan, a study by Ray and Ray (2012) in India and Ghosh (2012) which concluded that there is no causal relationship between economic growth and government spending in Pakistan and India. That is, these three studies do not support the Keynesian hypothesis or Wagner's law.…”
Section: Resultsmentioning
confidence: 99%
“…Another example would be private airports, which would have to pay federal and state taxes on earnings and property taxes at the local level and would cost more to consumers than the artificially low cost the public option affords (Edwards, 2013). Public spending does crowd out private spending (e.g., see Afonso & Sousa, 2012;Ghosh Roy, 2012;Landau, 1983;Voss, 2002). Crowding out only happens when the private sector would have otherwise provided the service.…”
Section: Costs Of Delayed Maintenancementioning
confidence: 99%
“…This contrasts with public spending in general, which is found to retard growth. The limited studies showing that government spending encourages economic growth find this relationship only when expenditures involve education, transportation infrastructure, and, less frequently, general infrastructure (for examples of this extensive literature, see Butkiewicz & Yanikkaya, 2011;Ghosh Roy, 2012;Hansson & Henrekson, 1994;Schaltegger & Torgler, 2006).…”
Section: Economic Developmentmentioning
confidence: 99%